Bribe payments under regulatory decentralization: Evidence from rights offering regulations in China - Liu, Ye; An, Yunbi; Zhang, Jinqing (Journal of Banking & Finance, 2016)
This paper investigates why and how firms’ bribe payments vary as a result of the interaction between firms and local public officials under the decentralized regulatory system for rights offerings implemented prior to 2001 in China. Using the gap between the estimated and reported total direct costs of rights offerings as a measure of firms’ bribes payments in the process of rights offering applications under this system, we find that bribe payments are positively related to local governments’ control rights, firms’ opportunity costs of refusing to pay bribes, and the severity of firms’ Jensen agency problems. We further show that after termination of the regulatory system, firms’ bribe payments are substantially reduced, and local governments’ control rights as well as the severity of firms’ Jensen agency problems can no longer explain the variation in bribe payments.